Digital impact on the marketing mix - Smith, PR (Henry Stewart Talks, 2010)
Web 2.0, Hyper competition, Customer engagement, Brand loyalty, Sustainable competitive advantage, The ladder of engagement principles, Collaborative co-creation, Ladder applied: cross industries, Ladder applied: specific case, Great Moments Of Sportsmanship campaign